A Preliminary Survey of Gastrointestinal Helminths of Murids (Rodentia: Muridae) at Five Selected Localities in Western Sarawak - Hamdan, Nur Elfieyra Syazana; Wan Ismail, Wan Nurainie; Abdullah, M.T. (Borneo Journal of Resource Science and Technology, 2016)
Field survey of gastrointestinal helminths on rodents from family Muridae were conducted at five localities in Western Sarawak from June 2013 until April 2014. A total of 31 host individuals comprising six species of murids were examined for gastrointestinal helminths using opportunistic necropsy. The hosts examined were Leopoldamys sabanus, Maxomys rajah, M. surifer, M. whiteheadi, Niviventer cremoriventer and Sundamys muelleri. Of these host species, 186 individuals consisting of two taxonomic groups of helminths were recovered, namely Nematoda and Cestoda. This study contributes to the growing literature on the infestation of endoparasites in rodents especially in Sarawak.